(untitled) (Analysis in Theory and Applications, 2012)
In this paper, we establish two weighted integral inequalities for commutators of fractional Hardy operators with Besov-Lipschitz functions. The main result is that this kind of commutator, denoted by H^α_b, is bounded from L^p_x^γ (R_+) to L^q_x^δ (R_+) with the bound explicitly worked out.